Inclusive special education: development of a new theory for the education of children with special educational needs and disabilities - Hornby, Garry (British Journal of Special Education, 2015)
Inclusive education and special education are based on different philosophies and provide alternative views of education for children with special educational needs and disabilities. They are increasingly regarded as diametrically opposed in their approaches. This article presents a theory of inclusive special education that comprises a synthesis of the philosophy, values and practices of inclusive education with the interventions, strategies and procedures of special education. Development of inclusive special education aims to provide a vision and guidelines for policies, procedures and teaching strategies that will facilitate the provision of effective education for all children with special educational needs and disabilities.